Steel cable failure analysis (2005)
This article describes the failure analysis performed on two samples of steel cables that suffered sudden failure under normal workload conditions. The fault was caused by a load less than the nominal capacity. After optical inspection it was evidenced that the fault was caused by fatigue of the material of one of the cables.